Perancangan dan Pembuatan Aplikasi Sistem Informasi Administrasi Pada PT. Swanindo Jaya - Chiptodjojo, Vincent; -, Yulia; Rostianingsih, Silvia (Jurnal Infra, 2015)
PT. Swanindo Jaya is a company engaged in the sale of machinery for industrial needs. PT. Swanindo Jaya was established in 2013 and is located at Jalan Haji Mansour Ki no. 168-170 Surabaya. PT. Swanindo Jaya established by a contractor experienced in the field and have knowledge of industrial machinery. The machine was obtained from local suppliers and foreign suppliers. Business processes in the PT. Swanindo Jaya consists of the buying process, sales, service and installation of the machine. The recording of the entire business processes in PT. Swanindo Jaya at this time is still running it manually. Over time, PT. Swanindo Jaya into a company that grew larger and larger. Business processes which occur also certainly going to walk more and complicated, so the recording process manually deemed no longer efficient. In accordance with the plan of the owner of PT. Swanindo Jaya, business processes will be designed more computerized and held the division of labor in a manner that is responsible for the establishment of the division in accordance with their respective roles.